2001
DOI: 10.1111/0002-9092.00175
|View full text |Cite
|
Sign up to set email alerts
|

Market Incentives for Safe Foods: An Examination of Shareholder Losses from Meat and Poultry Recalls

Abstract: Meat and poultry recalls, while voluntary, are carried out under governmental oversight. If firms have financial incentives to avoid being implicated in a recall situation, governmental involvement in recalls may cause firms to internalize social costs when making investment decisions concerning food safety controls. To examine these incentives, we analyze federally supervised meat and poultry recalls from 1982 to 1998 within an event study. Results show significant shareholder losses when publicly traded food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 14 publications
(2 reference statements)
1
101
0
Order By: Relevance
“…Although listeriosis is a relatively rare disease, mortality rates associated with outbreaks are high (29). Apart from the risk to human health, food product recalls due to Listeria contamination present an enormous financial burden, estimated to cost between $1.2 and $2.5 billion per year in the United States (30). Notably, in 2003 the Food Safety and Inspection Services (FSIS) published a ruling requiring manufacturers of ready-to-eat foods to provide additional post processing control measures to kill Listeria or prevent its growth, placing increased pressure on food manufacturers with respect to food safety.…”
Section: Discussionmentioning
confidence: 99%
“…Although listeriosis is a relatively rare disease, mortality rates associated with outbreaks are high (29). Apart from the risk to human health, food product recalls due to Listeria contamination present an enormous financial burden, estimated to cost between $1.2 and $2.5 billion per year in the United States (30). Notably, in 2003 the Food Safety and Inspection Services (FSIS) published a ruling requiring manufacturers of ready-to-eat foods to provide additional post processing control measures to kill Listeria or prevent its growth, placing increased pressure on food manufacturers with respect to food safety.…”
Section: Discussionmentioning
confidence: 99%
“…From a study on recall events in the automobile and pharmaceutical industry, it was concluded that the indirect costs are likely to be far greater than the direct costs (Jarrell & Peltzman, 1985). Therefore, food managers are willing to spend resources to provide a level of safety sufficient not only to protect consumers, but also to avoid costs associated with liability claims and the consequences of negative publicity and lost market share (Thomsen & McKenzie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Golub, Wilson and Featherstone (2005) examined stock price reactions to contamination of the corn supply with a genetically modified variety, StarLink, that had not been approved for human food use. Others have investigated events involving microbial or other contaminants that have resulted in food recalls on commodity prices or stock prices (Lusk and Schroeder, 2002;McKenzie and Thomsen, 2001;Thomsen and McKenzie, 2001). …”
mentioning
confidence: 99%